Long-term prescription opioid utilization, substance use disorders, and opioid overdoses after adolescent trauma. Issue 4 (October 2019) - Bell, Teresa M.; Raymond, Jodi; Vetor, Ashley; Mongalo, Alejandro; Adams, Zachary; Rouse, Thomas; Carroll, Aaron
Abstract : BACKGROUND: Injured adolescents have a 56% increased risk of developing a substance use disorder (SUD) within 3 years of their injury. The transition from medical prescription opioid use to nonmedical use in adolescent trauma patients has not been longitudinally studied long-term. The aim of this study is to describe 5-year patterns of opioid use in a cohort of injured adolescents as well as the proportion of patients experiencing overdose and SUD diagnoses. METHODS: Our retrospective cohort study consisted of 736 patients aged 12 years to 18 years who were admitted for trauma from 2011 to 2013. We examined up to 5 years of regional health information exchange data containing information on prescription fills as well as diagnoses from inpatient, outpatient, and emergency department encounters. RESULTS: At 1 year, over 20% of adolescents filled more than two opioid prescriptions after being discharged for their injury; and at 4 years, over 13% had received more than eight opioid fills. Over the 5-year period, 11% received an opioid antagonist injection, 14% received an SUD diagnosis, and 8% had an overdose diagnosis. Relatively few patients had diagnoses for other mental health conditions including depression (5.5%), posttraumatic stress disorder (2.1%), and chronic pain (3.6%). CONCLUSION: Opioid usage remains high for multiple years in a subset of the adolescent trauma population. Mental health diagnosis rates were substantially lower in injured adolescents than what has been reported in adults. However, overdose and SUD diagnoses occur in over 1 in 10 adolescents within 5 years of their injury. LEVEL OF EVIDENCE: Prognostic and epidemiological study, level IV.